The Development of Interactive E-Module based on Problem Solving in Physics Learning - Agustini, Sri; Hamzah, Ria Rezki (MACCA : Science-Edu Journal, 2024)
Objectives of this research are: (1) Producing an Interactive E-Moodle based on problem solving and analysis:(2) validator and teacher assessment results; (3) pupils perception result; (4) the effectiveness of use interactive E-Moodle based on problem solving in physics learning toward of student problem solving ability at Senior High School (SMAN) 5 Soppeng that has been developed. This is research and development using 4D model which steps are defining, designing, developing and disseminating. Trial subjects of research was using 9 pupils which held on SMAN 5 Soppeng. This research uses several instruments such as validator assessment sheets, teacher assessment questionnaire, student perception questionnaire, and Problem Solving test which was designed with an essay model. The average of validator and teacher assessments results are percentages of 77.60 and 81.89, respectively. Both percentages show good and very good category. The trial was done twice. First trial result shows that the average score of student test is 18.89 meanwhile, the average score of second trial is 19.67. Generally, the score of students is 19.00. Based on the test score we found that student categories in good and very good categories. In addition, student perceptions result of interactive E-Moodle shows in good and very good category. We can conclude that an Interactive E-Moodle based on Problem Solving is appropriate for use in physics learning.